2022
DOI: 10.1002/aoc.6950
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biogenic silver nanoparticles from the extract of Heliotropium eichwaldi L. and their effect as antioxidant, antidiabetic, and anti‐cholinesterase

Abstract: Recently, green nanotechnology has received much importance in different fields. It is concerned with the production of small-size nanoparticles (NPs).It is less toxic to human health and also environmentally benign. Heliotropium eichwaldi (HE) is an herbaceous weed and is widely distributed in Pakistan. The herb is used traditionally for earache, headache, cleaning, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 84 publications
3
14
0
Order By: Relevance
“…The current results are in good accordance with the previous report. [41,42] The present UV results are also supported by Sher et al [9] For the synthesis of unique NPs, an ideal environment is required, for example, pH, plant, reaction time, salt concentrations, temperature, and stability period. A previous report by Qian et al [43] confirmed that different intrinsic factors affect the yield of NPs.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The current results are in good accordance with the previous report. [41,42] The present UV results are also supported by Sher et al [9] For the synthesis of unique NPs, an ideal environment is required, for example, pH, plant, reaction time, salt concentrations, temperature, and stability period. A previous report by Qian et al [43] confirmed that different intrinsic factors affect the yield of NPs.…”
Section: Discussionsupporting
confidence: 85%
“…The FT‐IR Shimadzu (IR Prestige‐21) spectrometer (Japan) analysis of both plant HH and BNPs are shown in Figure 2. The different peaks that are exhibited by HH and their BNPs along with their corresponding phytochemicals and functional groups were confirmed by relating with the standard FT‐IR chart of Sher et al [ 40 ] See Table 1.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations